2016
DOI: 10.1007/s12574-016-0300-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chronic renal failure on cardiac function: an experimental study with a rat model

Abstract: The adenine-induced CRF rat model developed renal dysfunction and left ventricular diastolic dysfunction independent of the presence of hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…We have recently used this model and demonstrated that intratracheal instillation of diesel exhaust particles aggravate renal oxidative stress, inflammation, and DNA damage in mice with adenine-induced CKD (Nemmar et al, 2016a ). We and others have also used this model to show the occurrence of gastrointestinal or cardiovascular complications after the induction of CKD with adenine (Ali et al, 2013 , 2014b ; Diwan et al, 2013 ; Nakano et al, 2016 ). However, as far as we are aware, no study to date has investigated the in vivo pulmonary consequence of this valid and well-established model of CKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently used this model and demonstrated that intratracheal instillation of diesel exhaust particles aggravate renal oxidative stress, inflammation, and DNA damage in mice with adenine-induced CKD (Nemmar et al, 2016a ). We and others have also used this model to show the occurrence of gastrointestinal or cardiovascular complications after the induction of CKD with adenine (Ali et al, 2013 , 2014b ; Diwan et al, 2013 ; Nakano et al, 2016 ). However, as far as we are aware, no study to date has investigated the in vivo pulmonary consequence of this valid and well-established model of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…While the effect of adenine on the development of CKD has been widely investigated, little is known on the extra-renal impact of such model of CKD. Recently, it has been reported that adenine induce CKD and cardiovascular damage in rats including increased ventricular fibrosis, systolic blood pressure and left ventricular stiffness, left ventricular diastolic dysfunction independent of the presence of hypertension and impaired vascular responses (Diwan et al, 2013 ; Ali et al, 2014a ; Nakano et al, 2016 ). Since it has been reported that CKD is associated with effects on distant organs, including the lungs, in the present study, we wanted to test the hypothesis of the possible occurrence of pulmonary injury in animal model of CKD induced by adenine.…”
Section: Introductionmentioning
confidence: 99%
“…We combined this model with an oral diet of adenine to induce progression to CKD caused by precipitation of the adenine metabolite 2,8-dihydroxyadenine, which precip-itates into crystals to cause tubular damage (11,39). Although there are several models that simulate CKD, studies demonstrate that the adenine model closely mimics findings associated with CKD including progressive hypertension, uremia, anemia, and abnormal calcium dynamics (6,18,29,45). In addition, this model consistently exhibits renal inflammation and fibrosis as seen in CKD (11,22,28).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with CRF have an increased risk of cardiovascular diseases (CVD) (Couser and Riella 2011) such as cardiac fibrosis, hypertrophy, and dysfunction, i.e., uremic cardiomyopathy (Drummond et al 2016) with a higher risk of cardiovascular mortality (10 to 20-fold) than controls without kidney disease (Foley et al 1998). Although the mechanistic pathways employed in CRF impact on cardiac functions are not fully understood, hypertension, oxidative stress, and volume overload are considered common contributors (Garcia-Trejo et al 2016;Nakano et al 2016). The sodium/potassium-adenosine-triphosphatase (Na + /K + -ATPase) plays a key role in myocardial contractility through regulating the concentration of ions inside and outside cells.…”
Section: Introductionmentioning
confidence: 99%